The Psychometric Properties Of Measurement Of The Mathematics Teachers’ Professional Identity In Saudi Arabia - Abdullah J, Alghamdi Hamad (2021)
The primary purposes of the study are to assess the psychometric properties of the professional identity measure of Mathematics teachers and to explore the profile of the professional identity of Mathematics teachers in the Kingdom of Saudi Arabia. The descriptive approach is used in this study.